2022
DOI: 10.29303/jppipa.v8i6.2064
|View full text |Cite
|
Sign up to set email alerts
|

Development of VideoScribe Assisted Learning Media to Improve Understanding of Physics Concepts

Abstract: Penelitian ini adalah penelitian pengembangan yang bertujuan untuk: mendeskripsikan kelayakan media pembelajaran berbantuan video scribe, penilaian praktisi terhadap media pembelajaran berbantuan video scribe, efektivitas media pembelajaran berbantuan VideoScribe pada pembelajaran fisika, dan menghasilkan media pembelajaran berbantuan video scribe. Subjek uji coba penelitian ini adalah 20 orang peserta didik kelas XI IPA 3 SMAN 6 Sinjai. Penelitian ini menggunakan pengembangan model ADDIE. Instrumen yang digun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This can be proven from the results of the student response questionnaire on indicator number three which received an average score of 3.88 This result is supported by the opinion expressed by (Untari, 2017) he explained that the subject matter delivered will be more clearly conceptualized so that its meaning can be easily understood by students and the teaching methods carried out by teachers become more varied. Furthermore, (Melita et al, 2023) also revealed that learning media has an important role in learning activities because of its role as an intermediary for teachers in delivering messages or information, this is so that learning materials can be easily understood by students well. Learning media also acts as a useful supporting tool to clarify the meaning of a message conveyed, so that the role of the media can achieve learning objectives well (Andayani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This can be proven from the results of the student response questionnaire on indicator number three which received an average score of 3.88 This result is supported by the opinion expressed by (Untari, 2017) he explained that the subject matter delivered will be more clearly conceptualized so that its meaning can be easily understood by students and the teaching methods carried out by teachers become more varied. Furthermore, (Melita et al, 2023) also revealed that learning media has an important role in learning activities because of its role as an intermediary for teachers in delivering messages or information, this is so that learning materials can be easily understood by students well. Learning media also acts as a useful supporting tool to clarify the meaning of a message conveyed, so that the role of the media can achieve learning objectives well (Andayani et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of mathematics learning media are textbooks or textbooks. Quality packaged books can be effective learning media because they provide clear and systematic learning about mathematical concepts, besides that textbooks can also contain practice questions to test students' understanding (Maryatun, 2015;Silfiani et al, 2022) said that the source of the study was not only in printed form such as books that were spread on generally. But you can also use learning tools such as interactive videos, satellite communications, television, personal computers, e-mail and other multimedia computer technologies.…”
Section: Introductionmentioning
confidence: 99%